Внедрение логистических методов в управление финансами предприятий РФ (на примере оборотных активов) - Гревцова, Т.В. (Культура народов Причерноморья, 2013)
Рыночная экономика предполагает становление и развитие предприятий, основанных на
разных видах частной собственности. Деятельность этих предприятии в условиях жесткой
конкуренции ориентирована на получение и максимизацию прибыли, удержание устойчивой рыночной
позиции. Одним из главных факторов достижения этих целей является грамотное распоряжение
финансами предприятия, применение современных, эффективных методов управления. Внедрение
логистических методов в управление финансами предприятия (в частности оборотными активами)
будет способствовать минимизации издержек и своевременному удовлетворению потребительского
спроса.
Ключевые слова: финансы, управление финансами предприятия, оборотные активы, логистика,
логистические методы управления, метод АВС, XYZ-анализ. Ринкова економіка передбачає становлення і розвиток підприємств заснованих на різних
видах приватної власності. Діяльність цих підприємств в умовах жорсткої конкуренції орієнтована на
отримання і максимізацію прибутку, утримання стійкої ринкової позиції. Одним із головних чинників
досягнення цих цілей є грамотне розпорядження фінансами підприємства, застосування сучасних
ефективних методів управління. Впровадження логістичних методів управління фінансами
підприємства (зокрема оборотними активами ) сприятиме мінімізації витрат і своєчасного
задоволення споживчого попиту.
Ключові слова: фінанси, управління фінансами підприємства, оборотні активи, логістика, логістичні
методи управління, метод АВС, XYZ-аналіз. The market economy presupposes the establishment and development of enterprises based on the
different types of private ownership. Activity of the enterprise in conditions of a rigid competition is aimed at
obtaining and profit maximization, holding a stable position at the market. One of the main factors of achieving
these goals is the corresponding order of the finances of enterprise, the use of modern, effective methods of
management. For any company engaged in the production or other commercial activity, the integral part of the
assets are current assets , means of serving the process of economic activities, participating at the same time and
in the process of production, and in the process of realization of production. The presence at the enterprise of
own working capital predetermine the financial stability of its position on the market. The introduction of
logistics methods in the field of management of the circulating assets of the enterprise will contribute to
minimizing costs and timely satisfaction of a consumer demand. In article are considered questions of the
practical application of such logistics inventory management techniques of the enterprise, and ABC and XYZ
analysis. The material presented will be useful for the management of the enterprises, wishing to improve the
accounting of goods and services, reduce the cost of warehouse operations, increase efficiency of managing
circulating assets of the enterprise.
Keywords: Finance, financial management of the enterprise, the current assets, logistics, logistics management
methods, the method of ABC, XYZ-analysis.